2009
DOI: 10.1093/cvr/cvp030
|View full text |Cite
|
Sign up to set email alerts
|

Sphingomyelinases: their regulation and roles in cardiovascular pathophysiology

Abstract: Sphingomyelinases (SMases) hydrolyse sphingomyelin, releasing ceramide and creating a cascade of bioactive lipids. These lipids include sphingosine and sphingosine-1-phosphate, all of which have a specific signalling capacity. Sphingomyelinase activation occurs in different cardiovascular system cell types, namely cardiac myocytes, endothelial and vascular smooth muscle cells, mediating cell proliferation, cell death, and contraction of cardiac and vascular myocytes. Three main types of SMases contribute to ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
100
0
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 144 publications
(109 citation statements)
references
References 123 publications
4
100
0
5
Order By: Relevance
“…Since then nSMase2 has been established as a key regulator of exosome secretion and cell-stress responses and has been implicated in cancer (32,33), Alzheimer's disease (34,35), and cardiovascular disease (53). Based on our biochemical and structural experiments, we now are able to propose a model for the activation of nSMase2.…”
Section: Discussionmentioning
confidence: 88%
“…Since then nSMase2 has been established as a key regulator of exosome secretion and cell-stress responses and has been implicated in cancer (32,33), Alzheimer's disease (34,35), and cardiovascular disease (53). Based on our biochemical and structural experiments, we now are able to propose a model for the activation of nSMase2.…”
Section: Discussionmentioning
confidence: 88%
“…However, in mammalian organisms the role, function and regulation of S-ASM are not as well understood as those of L-ASM. Several previous reviews cover various aspects of S-ASM physiology and pathophysiology (Tabas, 1999;Goni and Alonso, 2002;Smith and Schuchman, 2008;Jenkins et al, 2009;Pavoine and Pecker, 2009;He and Schuchman, 2012). In this review, we focus on the progress made in recent years specifically on mammalian S-ASM and some aspects of secreted L-ASM, and we examine novel studies investigating S-ASM as a mediator of pathogenic processes, a potential therapeutic target and a biomarker in human diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Sphingomyelinase activity in cardiovascular cells results in release of ceramides which signals contraction of cardiac myocytes (68). It has been reported that inhibition of sphingomyelinase prevents cardiovascular diseases like atherosclerosis and thrombosis by reducing the production of ceramides (66).…”
Section: Cardiovascular Disordersmentioning
confidence: 99%